The Role of Teachers in Creating a Child-Friendly School at TK Negeri Pembina Gianyar Bali - Briliany, Noviarta; Laksemi, Anak Agung Ari (Kiddo: Jurnal Pendidikan Islam Anak Usia Dini, 2024)
Early childhood education is the first formal education that young children attend. Children’s joyful experiences at this educational stage become crucial because they lay the foundation for a love of learning, a love of education, and lifelong learning. In 2015, the Indonesian Government initiated the program of “Sekolah Ramah Anak” (Children-Friendly School) to serve the right of children to gain knowledge at schools. Teachers possess important roles in Children Friendly Schools. The purpose of this study is to investigate the role of teachers in a Children-Friendly School, TK Negeri Pembina Gianyar - Bali. This research applies the qualitative-descriptive method. The research method used is qualitative, the purpose of this study uses qualitative research so that researchers can describe a that occurs such as the role of teachers in child-friendly schools. The sample in this study was 11 teachers with a minimum teaching experience of 5 years. Data collection techniques in this study used interviews. Data analysis in this study was carried out through the stages of data reduction, data presentation, then conclusions (Miles and Huberman). The result explains that the teachers in TK Negeri Pembina Gianyar - Bali have various roles, such as facilitators, mentors, and motivators. They involve children, school staff, parents, and the community to establish a children-friendly environment.